2019
DOI: 10.1002/lary.28445
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of endolymphatic shunt surgery and intratympanic gentamicin for meniere's disease

Abstract: Objective To report audiovestibular outcomes following endolymphatic shunt surgery (ELS) and intratympanic gentamicin injections (ITG) in patients with Meniere's disease (MD). Study Design Retrospective matched cohort study Methods Patients with MD refractory to medical management between 2004 and 2017 were reviewed: 44 patients underwent ELS and had outcomes available, while 27 patients underwent ITG and had outcomes available. Mean follow‐up durations for the ELS and ITG groups were 39.1 and 43.3 months, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Moreover, a study by Gibson et al demonstrated similar classes A-B vertigo control between patients receiving ESS and those receiving intratympanic gentamycin injections (73.1% vs. 66.8%, p � 0.76). However, chronic posttreatment unsteadiness was encountered more frequently in the patients receiving intratympanic gentamycin injections compared to patients receiving ESS (25.0% vs. 0%, p � 0.009) [25]. Overall, we had classes A-B vertigo control in 79.17% of patients and decreased FLS from 4.2 to 2.8.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, a study by Gibson et al demonstrated similar classes A-B vertigo control between patients receiving ESS and those receiving intratympanic gentamycin injections (73.1% vs. 66.8%, p � 0.76). However, chronic posttreatment unsteadiness was encountered more frequently in the patients receiving intratympanic gentamycin injections compared to patients receiving ESS (25.0% vs. 0%, p � 0.009) [25]. Overall, we had classes A-B vertigo control in 79.17% of patients and decreased FLS from 4.2 to 2.8.…”
Section: Discussionmentioning
confidence: 69%
“…ESS is an attractive option because it avoids the total hearing loss and permanent vestibular dysfunction seen with labyrinthectomy. On the other hand, intratympanic gentamycin allows the patient to avoid the morbidity of a surgical procedure but has the potential to damage hearing and vestibular function [25]. Previous studies on ESS have demonstrated excellent vertigo control and improvements in FLS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 37 suggested that ESS with posterior tympanotomy and local steroid treatment could improve hearing and ensure a satisfactory vertigo control in patients with intractable MD. In Gibson et al opinion 38 , ESS can provide a vertigo control at least as well as IT gentamicin with a lower incidence of audio-vestibular complications 39 . Transmastoid labyrinthectomy alone 40 or in combination with cochlear implantation 41 , grommet insertion 42 , and triple semicircular canal plugging 43 have been proposed as an effective surgical option for the treatment of MD.…”
Section: Discussionmentioning
confidence: 97%
“…Mounting evidence supports the use of ELS surgery prior to consideration of intratympanic gentamicin with similar vertigo control. Gentamicin carries a risk of sensorineural hearing loss and a heightened incidence of chronic disequilibrium [45].…”
Section: Endolymphatic Sac Decompression: An Enduring Nonablative Sur...mentioning
confidence: 99%